2006
DOI: 10.1097/01.mao.0000244355.34577.85
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Residual Acoustic Hearing After Cochlear Implantation

Abstract: Conservation of pure-tone hearing was possible in 89% of implanted patients; however, residual speech perception was not conserved with this long perimodiolar electrode. A ceiling effect tends to inflate the prevalence of hearing conservation in implantation studies of severely to profoundly hearing-impaired patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
2
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(173 citation statements)
references
References 12 publications
5
152
2
13
Order By: Relevance
“…While Carlson et al (7), reported significantly better word perception scores in CI recipients with preserved residual hearing, Balkany et al (8), D'Elia et al (9), and Cosetti et al (10) could not demonstrate such an effect.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…While Carlson et al (7), reported significantly better word perception scores in CI recipients with preserved residual hearing, Balkany et al (8), D'Elia et al (9), and Cosetti et al (10) could not demonstrate such an effect.…”
mentioning
confidence: 86%
“…This could explain why other studies have reported no significant difference regarding word perception between patients with and without preservation of residual cochlear function. In the studies of Balkany et al (8), D'Elia et al (9), and Cosetti et al (10), the mean postoperative follow-up was 12 months or less. Still, although D'Elia et al found no significant difference in speech perception scores, they did find a correlation between hearing preservation and a larger dynamic range, which has been associated with better word perception in CI users in other studies (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing preservation is attempted for all co-chlear implant recipients with residual hearing nowadays [Carlson et al, 2011]. However, complete or partial loss of residual hearing still occurs in the majority of cochlear implant recipients [Anagiotos et al, 2015;Balkany et al, 2006]. The underlying mechanisms behind this hearing loss are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Any response reported as vibrotactile or questionably vibrotactile was classified as no response. Pure tone averages (PTAs) were calculated for 500, 1,000 and 2,000 Hz frequencies 14 . For speech testing, subjects were seated in a sound-treated room with the CI adjusted to the user's most comfortable listening setting.…”
Section: Postoperative Audiometric Evaluation With CImentioning
confidence: 99%